Tinjauan Waktu Pengembalian Rekam Medis Pasien Rawat Inap ke Unit Rekam Medis di Rumah Sakit X Jakarta Timur 2018 - Mutia Sari; Ima Rusdiana (APIKES Bhumi Husada Jakarta, 2018)
ABSTRACT At the East Jakarta Hospital X SOP the return of inpatient medical records in force is 2x24 in accordance with the theory of the 1991 Technical Guidelines for the Implementation of Medical Records and the Journal of Medicoeticolegal and Hospital Management in 2017 which states that the return time of inpatient medical records is 2x24 hours after the patient leaves treatment. The purpose of this study was to determine the policy and SOP regarding the return of medical records of inpatients in X Hospital in East Jakarta, calculate the payback time of medical records of patients who have been hospitalized, and identify the causes of inaccuracies in returning medical records of hospitalized patients. Obtained inaccuracies in return of inpatient medical records by 25% in April from a sample of 157 medical records of patients who left treatment. Lack of socialization regarding SOP in return of medical records of inpatients, lack of policies and job descriptions for returning inpatients' medical records and the length of time doctors complete patient medical records are factors that lead to inaccuracies in returning medical records of hospitalized patients. Keyword : Return of inpatient medical records